2021
DOI: 10.3389/fnbeh.2021.674127
|View full text |Cite
|
Sign up to set email alerts
|

A Rhesus Monkey Model of Non-suicidal Self-Injury

Abstract: Non-suicidal self-injury (NSSI) is a type of behavioral pathology seen not only in a variety of clinical conditions but also among non-clinical populations, particularly adolescents and young adults. With the exception of rare genetic conditions that give rise to self-harming behaviors, the etiology of NSSI and the events that trigger specific episodes of this behavior remain poorly understood. This review presents the features of an important, extensively studied animal model of NSSI, namely spontaneously occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 125 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Notably, the early onset of NSSI creates greater disease vulnerability. Studies have shown that individuals with NSSI onset younger than 12 years old tend to develop severe NSSI behaviors ( 12 ). Moreover, NSSI in early adolescence may predict the onset of mental disorders in late adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the early onset of NSSI creates greater disease vulnerability. Studies have shown that individuals with NSSI onset younger than 12 years old tend to develop severe NSSI behaviors ( 12 ). Moreover, NSSI in early adolescence may predict the onset of mental disorders in late adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…So even using the popular primate model, the rhesus macaque, it is challenging to imitate NSSI when accompanied by an affective disorder. 33 Therefore, we only selected the potential mechanisms research in humans.…”
Section: Methodsmentioning
confidence: 99%
“…Koska itsensä vahingoittamis ta esiintyy ja on esiintynyt useissa varsin erilai sissa yhteiskunnissa (18), on varsin mahdollista, että sitä on tavattu myös ennen kirjoitettua his toriaa eläneissä ihmisyhteisöissä. On myös ha vaittu, että ihmisten lisäksi myös muut eläimet vahingoittavat itseään, erityisesti vankeudessa elävät yksilöt (19)(20)(21)(22)(23).…”
Section: Haitalliset Lapsuudenkokemukset Ja Lapsuusperheen Sosioekono...unclassified